Heritability for IBMI index of Italian buffaloes used in artificial insemination - José Raúl Pérez-González; Néstor Simón Montiel-Urdaneta (Revista Científica)
The Italian National Association of Buffalo Breeders “ANASB”, as of February 2018, introduced innovations, and according to these considerations, the indexes for productive and morphological traits have been calculated using a multi-character model that replaces the IQM index. The IBMI index aims to obtain better animals both from the productive point of view and their morphological and functional characteristics. The IBMI is a value that can be heritable. Since it is a product of productive